Lokalni sistem DGPS - Stopar, Bojan (Geodetski vestnik, 1997)
The paper explains the fundamentals of the differential GPS (DGPS) positioning technique. A brief review of the local DGPS system is given. An analysis of system operation is presented especially with regard to the accuracy of determined DGPS positions in real time and in the postprocessing mode.
Keywords: določanje položaja; geodezija; GPS; natančnost določitve položaja